2021
DOI: 10.1111/coa.13842
|View full text |Cite
|
Sign up to set email alerts
|

Improving safety for day case adenotonsillectomy in paediatric obstructive sleep apnoea

Abstract: Paediatric obstructive sleep apnoea (OSA) is characterised by stertor, intermittent oxygen desaturation and repeated nocturnal awakening. 1 If left untreated, it can have significant repercussions, such as cor pulmonale, growth and developmental delay. 2 Adenotonsillectomy has proven to be effective in improving OSA outcomes in the majority of children. 3 Tonsillectomy (with or without adenoidectomy) is the most frequent ENT procedure comprising of 17% of the workload in the UK. 4 There has been an effort in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(27 citation statements)
references
References 9 publications
2
25
0
Order By: Relevance
“…2,4,[8][9][10][11][12][13][14][15][16][17][18][19][20] See Figure 1 for a PRISMA flow diagram illustrating the study selection process. 2,4,[8][9][10][11][12][13][14][15][16][17][18][19][20] All included studies were observational: 14 retrospective and one prospective. 12 One study had a control group for outcome comparison.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…2,4,[8][9][10][11][12][13][14][15][16][17][18][19][20] See Figure 1 for a PRISMA flow diagram illustrating the study selection process. 2,4,[8][9][10][11][12][13][14][15][16][17][18][19][20] All included studies were observational: 14 retrospective and one prospective. 12 One study had a control group for outcome comparison.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies did not report on how OSA was diagnosed in their population. 9,13,14,17,18 Three studies diagnosed OSA by using typical clinical symptoms, 10,19,20 and in another three studies the clinical diagnosis was confirmed by sleep studies or polysomnography (PSG) in some of the patients. 8,12,15 Four studies only included PSG-confirmed cases.…”
Section: Ascertainment Of Osamentioning
confidence: 99%
See 3 more Smart Citations